2017
DOI: 10.1139/cjas-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Variation in fur farm and wild populations of the red fox, Vulpes vulpes (Carnivora: Canidae). Part II: Craniometry

Abstract: The skulls of 165 red foxes (75 wild and 90 farm-bred individuals) collected in Poland in the years 2012-2014 were measured, analysed, and compared to further investigate the effect of ancestry and selective breeding on craniometrical variation between wild and farm red fox populations. Univariate comparisons of skull measurements (19 cranial traits), as well as four craniometric indices, revealed significant differences among vast majority of the studied measurements. Principal component analyses and two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…If the farm population originated from North American red foxes, then the admixture analysis would show a higher level of non‐native alleles (imported from North America) and a lack or low level of alleles of Eurasian origin. Earlier morphological studies and preliminary results of microsatellite markers analysis (Zatoń‐Dobrowolska et al., , ) have suggested that the origin of foxes and selective breeding played a significant role in the differentiation of morphological traits in Polish farm‐ and wild red foxes. However, to the best of our knowledge, only Jeżewska‐Witkowska et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the farm population originated from North American red foxes, then the admixture analysis would show a higher level of non‐native alleles (imported from North America) and a lack or low level of alleles of Eurasian origin. Earlier morphological studies and preliminary results of microsatellite markers analysis (Zatoń‐Dobrowolska et al., , ) have suggested that the origin of foxes and selective breeding played a significant role in the differentiation of morphological traits in Polish farm‐ and wild red foxes. However, to the best of our knowledge, only Jeżewska‐Witkowska et al.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive comparative research taking into account both morphological traits and molecular markers (microsatellites and mtDNA) has recently been carried out by Zatoń‐Dobrowolska et al. () and Zatoń‐Dobrowolska, Moska, Mucha, Wierzbicki, and Dobrowolski (), who investigated the effect of ancestry and selective breeding on morphological differences between wild‐ and farm‐bred red fox populations in Poland. They found significant differences among the vast majority of the body, cranial and dental measurements studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism comparisons. Sexual dimorphism within a species is often represented as dimorphism in size as well as shape 25 . Therefore, in contrast to the previous analyses, we assess the degree of sexual dimorphism in both size and shape.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Yapılan literatür araştırmalarında kızıl tilki osteolojisi üzerindeki çalışmaların genellikle cranium ve appendicular iskelet üzerinde olduğu görülmüştür. Örneğin; kemik üzerinden craniometrik ve osteometrik ölçümlerin yapıldığı (16,17), appendicular iskeletin morfolojisi ve morfometrisinin (18) ortaya konulduğu, vücudunun ve cranium'unun morfometrik ölçümlerinin (15,19) alındığı, scapula'sının 3B rekonstrüksiyonu üzerinden morfometrik ölçümlerinin yapıldığı (20) çalışmalardır. Fakat columna vertebralis'in 3B rekonstrüksiyonun ortaya konulduğu ve morfometrik ölçümlerinin gerçekleştiği herhangi bir çalışmaya rastlanılmamıştır.Bu çalışma MDBT görüntüleri kullanarak üç boyutlu bilgisayar programı aracılığı ile elde edilen 3B rekonstrüksiyonlara dayanarak tilki cervical vertebrae'nın morfometrik özelliklerinin belirlenmesi amacıyla yapılmıştır.…”
Section: Araştırma Makalesiunclassified